Digging Deeper into Supply Risk: A Systematic Literature Review on Price Risks. Issue 5 (21st August 2014) - Fischl, Maria Christine; Scherrer-Rathje, Maike; Friedli, Thomas
Abstract : Purpose: Risks related to the purchase prices of industrial consumption factors (raw materials, semi-finished/finished goods, auxiliary materials, and operating materials) exert an increasing influence on manufacturing companies' business continuity and economic sustainability. The aim of this paper is both to provide an overview of existing knowledge pertaining to the management of price risks in manufacturing companies from an operations management (OM) perspective and to establish an agenda for future research. Design/methodology/approach: A systematic literature review was conducted following the literature search approach of vom Brocke et al. (2009). In total, 138 relevant articles were identified, analysed, and synthesised. Findings: The literature review reveals that the existing OM literature devotes little attention to price risks and their management in manufacturing companies. In particular, further empirical investigation is required to support decision-making in various risk contexts. Originality/value: To the best of the authors' knowledge, this is the first literature review to focus on price as a specific supply risk.